2021
DOI: 10.1007/s42235-021-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Anti-corrosion Performance of NiTi Alloy in Human Body Solution with the Fabricating Processes of Laser Irradiation and PDMS Modification

Abstract: This paper presents a new and safe method of fabricating super-hydrophobic surface on NiTi Shape Memory Alloy (SMA), which aims to further improve the corrosion resistance performance and biocompatibility of NiTi SMA. The super-hydrophobic surfaces with Water Contact Angle (WCA) of 155.4° ± 0.9° and Water Sliding Angle (WSA) of 4.4° ± 1.1° were obtained by the hybrid of laser irradiation and polydimethylsiloxane (PDMS) modification. The forming mechanism was systematically revealed via Scanning Electron Micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The larger the diameter, the greater the corrosion resistance of the material. [ 26 ] NiTi‐V had the largest diameter, followed by NiTi‐III and NiTi‐I, while NiTi‐II and NiTi‐IV had the smallest diameters. As shown in Figure 5b, at the low frequency from 0.01 to 0.1 Hz, the impedance modulus | Z | ranks as follows: | Z | (NiTi‐V) > | Z | (NiTi‐III) > | Z | (NiTi‐I) > | Z | (NiTi‐IV) > | Z | (NiTi‐II) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The larger the diameter, the greater the corrosion resistance of the material. [ 26 ] NiTi‐V had the largest diameter, followed by NiTi‐III and NiTi‐I, while NiTi‐II and NiTi‐IV had the smallest diameters. As shown in Figure 5b, at the low frequency from 0.01 to 0.1 Hz, the impedance modulus | Z | ranks as follows: | Z | (NiTi‐V) > | Z | (NiTi‐III) > | Z | (NiTi‐I) > | Z | (NiTi‐IV) > | Z | (NiTi‐II) .…”
Section: Resultsmentioning
confidence: 99%
“…The treated samples, a Pt plate (20 mm × 20 mm × 0.1 mm) and a saturated calomel electrode were used as the working, counter, and reference electrodes, respectively. [ 26 ] The working electrode, with a surface area of 1 × 1 cm 2 , was exposed to Hank's solution. The compositions of the solutions are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, laser texturing has been increasingly used in the preparation of superhydrophobic surfaces and corrosion-resistant fields in recent years due to its advantages, such as processing efficiency, strong controllability, and low pollution. By imitating examples of superhydrophobicity in nature, such as lotus, water strider leg, fish scale, reed leaf, and so on, a micronanocomposite structure was established on the surface using laser texturing, and a superhydrophobic surface was prepared by adsorbing organic matter to reduce surface energy. The general methods for adsorbing organic matter can be divided into placing and using modifiers in the air, with the latter having better effectiveness and rapidity. Further research has found that superhydrophobic surfaces have enhanced salt corrosion resistance compared to the pristine surface, improving the service life of metals in production and usage. There are several reasons for this corrosion resistance effect. First, the surface structure is a significant factor.…”
Section: Introductionmentioning
confidence: 99%